PBNS 184- A New Safflower High Oil Yield Variety for Zone I : PBNS 184- A New Safflower High Oil Yield Variety for Zone I - S B GHUGE; S A SHINDE; C V AMBADKAR; V R GHUGE (Journal of Oilseeds Research, 2023)
A new safflower variety PBNS-184 evaluated in coordinated trials at twenty locations under rainfed and irrigated conditions during 2018-2021 for seed and oil yield as well as reaction to biotic stresses viz; Alternaria leaf spot, Fusarium wilt and aphid pest in comparison with the national checks A-1 and PBNS-12 AICRP testing programme has recorded 11.26 and 14.39% higher oil yield over checks and was found moderately resistant to Fusarium wilt and tolerant to Alternaria leaf spot disease reaction. It was also moderately tolerant to aphid pest as compared with all other qualifying varieties and checks. Hence, the variety PBNS -184 was released for cultivation in Zone-I i.e. Maharashtra, Karnataka, Telangana and Andhra Pradesh by project.